Anisotropic sliding on dual-rail hydrophilic tracks. Issue 6 (15th February 2017) - Yang, Xiaolong; Song, Jinlong; Zheng, Huanxi; Deng, Xu; Liu, Xin; Lu, Xiaohong; Sun, Jing; Zhao, Danyang
Abstract : Potential intelligent lab-on-a-chip applications were explored based on the discussion of multidimensional anisotropic sliding on milled dual-rail hydrophilic micro-tracks. Abstract : Biomimetic surfaces with sliding angle (SA) anisotropy have the capacity to directionally control the motion of water droplets and therefore have wide applications in various domains. Parallel and narrowing dual-rail hydrophilic tracks (DRHTs) are fabricated on etched superhydrophobic Al surfaces using a micromilling technique. Orthogonal and linear SA anisotropies are observed and investigated on the parallel and narrowing DRHTs, respectively. Track spacings of the parallel DRHTs are designed to regulate the orthogonal SA anisotropy of the water droplet. Experimental data shows that the along-track droplet–substrate interfacial widths, together with the sliding anisotropy, decrease with the increase of the track spacings. SA contrast (linear SA anisotropy) in two opposite directions along the tracks is observed and discussed on the narrowing DRHTs. Results indicate that droplets slide with more difficulty in the spacing-expanding direction than those in the shrinking direction, and when a droplet is dispensed at the tail end of a DRHT segment, the along-track outward detaching SAs and inward SAs also show sharp linear anisotropy due to the droplet–track interfacial liquid tension. On the basis of the discussed orthogonal and linear SAs, potential lab-on-a-chip applications for intelligent droplet transport, mixing and capture & release are explored.